Evaluating Students’ Achievement Test in Reading for Interpretation - Aisyah, Aisyah (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
Reading is one of the important subjects in learning foreign language. Based on the curriculum 2014 in English Department, reading has some series. In order to get satisfying result of students in reading comprehension, the lecturer should know about the students’ achievement in comprehending the text. By knowing students’ achievement in reading for interpretation, the lecturer will know what they will do for the next and what should the lecturer give more attention to. This research is aimed to know the students’ achievement in comprehending the text. The subject of this research is the first year students of English department.This research is expected to give contribution for some aspects. For the students, it is expected to give information and feedback to the students about their competence in reading. For the teacher, this research is expected to give information for the lecturer about the students’ error in comprehending the text.